Transforming travel : realising the potential of sustainable tourism - Smith, Jeremy 1973- (CABI, 2018)
"Transforming Travel combines stories from leading companies, interviews with pioneers and thinkers, along with thorough analysis of the industry's potential to make lasting, positive change. - A unique collection of case studies and stories of the most successful, inspirational, impactful and innovative travel businesses in the world. - A vital presentation of the latest research and statistics on the positive impacts and potential of transformative, sustainable tourism, - A positive and realistic vision of the scope of tourism to promote sustainable development at a time when travel and interaction with foreign cultures is facing numerous existential challenges. Written in a highly engaging style Transforming Travel presents an urgent argument for transforming tourism so it might reach its potential to promote tolerance, restore communities and regenerate habitats, while providing a vital guide for anyone looking to develop the successful sustainable tourism enterprises and destinations needed to do so"--Resumé vydavatele
Keywords: udržitelný cestovní ruch; cestovní ruch -- environmentální aspekty; sustainable tourism; tourism -- environmental aspects; studie; studies